Boundary stories: Constructing the Validation Centre in West Sweden - Diedrich, Andreas; Walter, Lars; Czarniawska, Barbara (Scandinavian Journal of Public Administration, 2011)
The role of stories in organizing has traditionally been examined within the context of specific organizations, communities of practice, or social worlds. The study reported here describes the establishment in West Sweden of a centre for developing methods that allow for the recognition of prior learning in people seeking employment. In the report, we highlight the role of stories and storytelling in coordination and organizing between and among organizations, but also between and among social worlds. We refer to such stories as boundary stories, and argue that they are not only the means for creating a shared understanding and facilitating joint actions among a number of public and private organizations, but that they also help to hide potential conflicts, paradoxes, and contradictions among actors.